Efficacy of LAMB against Emerging Azole- and Multidrug-Resistant Candida parapsilosis Isolates in the Galleria mellonella Model - Binder, Ulrike (J Fungi (Basel), 2020)
While being the third leading cause of candidemia worldwide, numerous studies have shown severe clonal outbreaks due to fluconazole-resistant (FLCR) Candida parapsilosis isolates associated with fluconazole therapeutic failure (FTF) with enhanced mortality. More recently, multidrug resistant (MDR) C. parapsilosis blood isolates have also been identified that are resistant to both azole and echinocandin drugs. Amphotericin B (AMB) resistance is rarely reported among C. parapsilosis isolates and proper management of bloodstream infections due to FLZR and MDR isolates requires prompt action at the time of outbreak. Therefore, using a well-established Galleria mellonella model, we assessed whether (a) laboratory-based findings on azole or echinocandin (micafungin) resistance in C. parapsilosis lead to therapeutic failure, (b) LAMB could serve as an efficient salvage treatment option, and (c) distinct mutations in ERG11 impact mortality. Our in vivo data confirm fluconazole inefficacy against FLCR C. parapsilosis isolates carrying Y132F, Y132F + K143R, Y132F + G307A, and G307A + G458S in Erg11p, while LAMB proved to be an efficacious accessible option against both FLCR and MDR C. parapsilosis isolates. Moreover, positive correlation of in vitro and in vivo data further highlights the utility of G. melonella as a reliable model to investigate azole and polyene drug efficacy.